Fault slip envelope: a new parametric investigation tool for fault slip based on geomechanics and 3-D fault geometry - Soliva, Roger; Maerten, Frantz; Maerten, Laurent; Mattila, Jussi (Solid Earth, 2019)
International audience By combining a 3-D boundary element model, frictional slip theory, and fast computation method, we propose a new tool to improve fault slip analysis that allows the user to analyze a very large number of scenarios of stress and fault mechanical property variations through space and time. Using both synthetic and real fault system geometries, we analyze a very large number of numerical simulations (125 000) using a fast iterative method to define for the first time macroscopic rupture envelopes for fault systems, referred to as "fault slip envelopes". Fault slip envelopes are defined using variable friction, cohesion, and stress state, and their shape is directly related to the fault system 3-D geometry and the friction coefficient on fault surfaces. The obtained fault slip envelopes show that very complex fault geometry implies low and isotropic strength of the fault system compared to geometry having limited fault orientations relative to the remote stresses, providing strong strength anisotropy. This technique is applied to the realistic geological conditions of the Olkiluoto high-level nuclear waste repository (Finland). The model results suggest that the Olkiluoto fault system has a better ability to slip under the present-day An-dersonian thrust stress regime than for the strike-slip and normal stress regimes expected in the future due to the probable presence of an ice sheet. This new tool allows the user to quantify the anisotropy of strength of 3-D real fault networks as a function of a wide range of possible geological conditions and mechanical properties. This can be useful to define the most conservative fault slip hazard case or to account for potential uncertainties in the input data for slip. This technique therefore applies to earthquake hazard studies, geological storage, geothermal resources along faults, and fault leaks or seals in geological reservoirs.